Alloyed Au/Pd nanoparticles formed by laser ablation of thin films in liquid. (1st May 2022) - Nastulyavichus, A A; Shelygina, S N; Khaertdinova, L F; Rudenko, A A; Kirilenko, D A; Kudryashov, S I; Ionin, A A
Abstract: The formation of alloyed Au/Pd nanoparticles (NPs) from thin magnetron-deposited Au–Pd films by nanosecond laser ablation in water is investigated. The films weight loss dependence is studied by thickness, intensity and laser pulses per point. Prepared NPs are transferred onto the silica wafer and characterized by scanning and transmission electron microscopy as well as optical and energy-dispersive x-ray spectroscopies. NPs size distribution was obtained using the dynamic light scattering (DLS) method.